'Smart home' in the statutory housing sale agreements in Malaysia? - Md Dahlan, Nuarrual Hilal; Yeon, Asmah Laili; Mohamed Yusoff, Zuryati; Mahdzir, Nazli; Basarudin, Noor Ashikin (2018)
Today’s ‘smart home’ is a popular notion referring to houses provided with automation and technological devices. The purpose of ‘smart home’ is to enhance safety and security and to provide environmental friendly and energy saving houses. Insofar as the situation in Malaysia is concerned, there is no official definition of ‘smart home’. Neither is there any legal and administrative policy on it. Likewise there is no specific law governing ‘smart home’. Thus, the definition and governance of smart home is unclear. This paper aims to discuss ‘smart home’ vis-à-vis the terms and conditions in statutory housing sale agreements in Peninsular Malaysia. This paper uses legal and qualitative social research methodologies to examine the features and issues of ‘smart home’ under the said housing sale agreements. The outcome of this paper can help policy makers to shape up and improvise the legal features and characteristics of ‘smart home’ in Malaysia